(untitled) (INNOVATIVE ECONOMY, 2024)
Shpatakova O.L. ENERGY EFFICIENCY MANAGEMENT STRATEGIES OF CONSTRUCTION ENTERPRISES: TYPES AND FEATURES Purpose. The aim of the article is to systematize the modern types and features of energy efficiency management strategies of construction enterprises. Methodology of research. The method of systematization was used in research, which made it possible to classify the leading strategies of the specified category. The characteristics of the evaluated strategies were established with the help of the induction method, determined by the analysis of individual provisions of scientific works. Findings. Features of modern types of energy efficiency management strategies of construction enterprises are singled out and defined, including: strategies of intelligent energy efficiency management in the construction of office buildings, intersectoral network strategies of energy efficiency management, which include the participation of construction enterprises as structural participants, the strategy of standardization, certification and specifications of energy management of construction enterprises. The systematization of strategies of this type was carried out on the basis of the analysis of the provisions of scientific approaches of foreign authors and it was proved that their selected types are innovative, as they are based on modern models of interaction of participants, mechanisms that are acceptable for the current conditions of ICT development in the field of the construction sector. It has been established that the reference to the defined strategies can make it possible to improve the level of energy efficiency of construction enterprises and construction objects in the conditions of the development of a sustainable society and economy, aimed at the energy transition from fossil fuels and renewable energy, saving energy use. It was found that the implementation of strategies of the specified type has an effect both for socially responsible construction enterprises and for those that are focused only on compliance with existing norms and requirements. It is noted that the adaptation of the specified strategies to the conditions of operation of construction enterprises of Ukraine can be carried out given the fact that there are different positions of the business sector in this field. It was determined that the adoption of the trend of society and consumers regarding the choice of construction objects that have high energy saving indicators and involve the use of renewable energy is relevant for making decisions about the transition to energy efficiency of construction enterprises. Originality. The theoretical provision of types and features of modern energy efficiency management strategies of construction enterprises has gained further development. Practical value. The strategies identified in the study can be implemented in the conditions of Ukrainian construction enterprises, focused on achieving their own energy efficiency and energy efficiency of construction objects. Key words: energy efficiency, construction enterprises, CO2, construction objects, cross-sectoral network strategies, standardization, certification and specification of energy management, ICT, energy transition.